Kasy, Maximilian. The Means of Prediction: How AI Really Works (and Who Benefits) - Autor, David (Journal of Economic Literature, 2026)
David Autor of Massachusetts Institute of Technology and NBER reviews “The Means of Prediction: How AI Really Works (and Who Benefits)” by Maximilian Kasy. The Econlit abstract of this book begins: “Presents a framework for understanding how artificial intelligence (AI) will proceed in a society that is shaped by power and inequality, focusing on the limits of AI and how it can be made to work for all people.”